The Continuity of Classical Arabic Language Pedagogy : Muhadatsah Method And Its Application In Modern Maharah Kalam Learning - Nofesalya, Katrin Adjma; Yul, Widiya; Andrian, Riko (Shaut al Arabiyyah, 2025)
This study examines Kalam learning through the Muhadatsah method at Ma’had Al-Jamiah, identifying supporting and inhibiting factors. A phenomenological approach with an interpretive paradigm and descriptive qualitative methods was used. Findings include: 1) The method aims to accustom students to Arabic communication. 2) Muhadatsah is significant due to its relaxed, practical nature, conversation habituation, repetitive practice, engaging elements, memorization facilitation, and fluency development. 3) Progress is assessed by students’ fluency and ease in pronunciation. 4) Implementation involves vocabulary assignments, partner selection, topic determination, and location choice for Muhadatsah. 5) Evaluation is through direct supervision by the instructor. 6) The teaching approach is relaxed and flexible. 7) No media are used as learning resources. 8) Challenges include limited time, an unsupportive language environment, students’ lack of basic Arabic knowledge, and shyness. 9) Success is seen in improved Kalam skills, accurate pronunciation, and increased vocabulary.